Crude nation : how oil riches ruined Venezuela - Gallegos, Raul, 1973- (Lincoln : Potomac Books, an imprint of the University of Nebraska Press, 2016)
"Beneath Venezuelan soil lies an ocean of crude--the world's largest reserves--an oil patch that shaped the nature of the global energy business. Unfortunately, a dysfunctional anti-American, leftist government controls this vast resource and has used its wealth to foster voter support, ultimately wreaking economic havoc. Crude Nation reveals the ways in which this mismanagement has led to Venezuela's economic ruin and turned the country into a cautionary tale for the world. Raul Gallegos, a former Caracas-based oil correspondent, paints a picture both vivid and analytical of the country's economic decline, the government's foolhardy economic policies, and the wrecked lives of Venezuelans. Without transparency, the Venezuelan government uses oil money to subsidize life for its citizens in myriad unsustainable ways, while regulating nearly every aspect of day-to-day existence in Venezuela. This has created a paradox in which citizens can fill up the tanks of their SUVs for less than one American dollar while simultaneously enduring nationwide shortages of staples such as milk, sugar, and toilet paper. Gallegos's insightful analysis shows how mismanagement has ruined Venezuela again and again over the past century and lays out how Venezuelans can begin to fix their country, a nation that can play an important role in the global energy industry"--
"Crude Nation tells the story of how ruinous mismanagement has resulted in the economic implosion of Venezuela, the country with the largest oil reserves in the world"--
1-800-LEO -- Infinite wants -- Let there be oil -- Everyman -- Funny business -- Oil for the people -- Mango management.
Includes bibliographical references and index.
104986
Keywords: 2000-2099; Petroleum industry and trade -- Venezuela -- History -- 21st century; Financial crises -- Venezuela -- History -- 21st century; Economic Conditions; International -- Economics; Venezuela -- Economic conditions -- 21st century; History